2018
DOI: 10.1111/trf.14634
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of D– red blood cell transfusion and rituximab therapy in autoimmune hemolytic anemia with anti‐D and panreactive autoantibodies arising after hematopoietic stem cell transplant

Abstract: In severe AIHA, when standard treatment and regular RBC transfusions are ineffective, transfusion of RBCs lacking the target antigen(s) of autoantibodies and administration of anti-CD20 MoAb should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…27,28 Several previous studies also reported that rituximab could be used for DSA desensitization in patients receiving Haplo-HSCT. 21,[29][30][31][32] Recently, Chang et al 33 demonstrated that treating DSA-positive patients with a single dose of rituximab significantly decreased levels of DSA MFI and reduced primary PGF in patients with DSA 2000 ≤ MFI < 5000. In our protocol, a single dose of rituximab (375 mg/m 2 ) was administrated after completion of DFPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Several previous studies also reported that rituximab could be used for DSA desensitization in patients receiving Haplo-HSCT. 21,[29][30][31][32] Recently, Chang et al 33 demonstrated that treating DSA-positive patients with a single dose of rituximab significantly decreased levels of DSA MFI and reduced primary PGF in patients with DSA 2000 ≤ MFI < 5000. In our protocol, a single dose of rituximab (375 mg/m 2 ) was administrated after completion of DFPP.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab has been demonstrated to be effective in dealing with DSA‐mediated organ transplant rejection 27,28 . Several previous studies also reported that rituximab could be used for DSA desensitization in patients receiving Haplo‐HSCT 21,29–32 . Recently, Chang et al 33 demonstrated that treating DSA‐positive patients with a single dose of rituximab significantly decreased levels of DSA MFI and reduced primary PGF in patients with DSA 2000 ≤ MFI < 5000.…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of biological target therapies, a significant improvement of post-allo-HSCT AIHA outcome has been observed. In particular, rituximab induced a response in about 49% of cases in 2nd line (lower than in primary AIHA), and in 88% of cases as 1st line, combined to steroid treatment (comparable to primary cases), again without distinguishing for AIHA type 2326. In particular, in a study by Sanz et al, 3/4 cases responded to rituximab frontline (2 CR and 1 PR), and 4/4 as second-line treatment (all PR) 23.…”
Section: Biological Treatments For Post-allo-hsct Aihamentioning
confidence: 99%